Coupled discrete-continuum approach for railway ballast track and subgrade macro-meso analysis. Issue 13 (10th November 2021) - Shi, Can; Zhao, Chunfa; Zhang, Xu; Guo, Yunlong
ABSTRACT: This paper presents a multi-layer railway ballast track and substructure model, where a coupled discrete and continuous method is used for macro-meso dynamic behaviour analysis under moving wheel loads. In this coupled model, the discrete element method (DEM) is utilised to build the superstructure of the ballast track (i.e. rail, fastener, sleeper and ballast layer), which considers the complex ballast shape and particle size distribution from mesoscopic level. The finite difference method (FDM) is used to simulate the substructure (i.e. subgrade and foundation) with a consideration of computing cost. And then, the coupled model is achieved by satisfying displacement, velocity and contact force compatibility between the FLAC and the PFC. Finally, the dynamic analysis is carried out by applying the wheel-rail forces obtained from a vehicle-track dynamics model into the coupled model. The DEM parameters of ballast particles are calibrated based on the results of the ballast direct shear tests, and the dynamic behaviour of railway ballast track and subgrade system is validated with the field measurement. Through the numerical analysis, it is confirmed that the coupled DEM/FDM model can reliably reflect macro-meso dynamic behaviour and accurately reveal the contact characteristics between the ballast layer and subgrade.